Experimental study on the feasibility of alternative materials for tilting pad thrust bearings operating in transition to mixed friction - Michał Wasilczuk; Michał Wodtke (Friction)
Abstract In hydrodynamic bearings traditional bearing alloys: Babbitts and bronzes are most frequently utilized. Polymer sliding layers are sometimes applied as a valuable alternative. Hard diamond-like carbon (DLC) coatings, which are also considered for certain applications may show some advantages, as well. Although material selection is of secondary importance in a full film lubrication regime it becomes important in mixed friction conditions, which is crucial for bearings with frequent starts and stops. Experimental research aimed at studying the performance of fluid film bearings in the specific operating regime, including the transition to mixed friction, is described in the paper. The tests were carried out on four tilting pad bearings of different material compositions: Steel/bronze, DLC/steel, steel/polyether ether ketone (PEEK), and steel/Babbitt. The tests comprised stopping under load and reproduction of the Stribeck curve by decreasing rotational speed to very low values, and observing the changes of friction force during the transition to mixed friction regime. Analysis of the transition conditions and other results showed clear differences between the tested bearings, illustrating the feasibility of less popular material compositions for bearings operating in specific conditions. More specifically, the DLC/steel bearing was demonstrating superior performance, i.e. lower friction, transition to mixed friction occurring at higher load, and more stable performance at start-stop regime over the other tested bearings.